2016
DOI: 10.1007/978-3-319-33622-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Task Allocation in Distributed Software Development Aided by Verbal Decision Analysis

Abstract: One of the most critical activities in distributed project management is the allocation of tasks among remote teams. In distributed software development projects, to allocate a task for a team in any of the locations, the project manager needs consider several factors such as team maturity and time zone difference among the sites. Deciding which task to allocate for each team constitutes a decision-making task. This decision is usually made subjectively. The verbal decision analysis is an approach based on sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The criteria values were ordered from the most preferable value to the least preferable one. As result of this step, we got the list of criteria and criteria values for the problem of selecting the most important factors to be considered in task allocation in DDS projects, which is listed next [33]:…”
Section: A Identification Of the Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria values were ordered from the most preferable value to the least preferable one. As result of this step, we got the list of criteria and criteria values for the problem of selecting the most important factors to be considered in task allocation in DDS projects, which is listed next [33]:…”
Section: A Identification Of the Influencing Factorsmentioning
confidence: 99%
“…We then selected the value of the criterion that had the greatest number of choices to represent the alternative. Table 2 [33] We emphasize that the various answers given by professionals, considering they have experienced project managers, were related to the fact that they have different professional backgrounds. Thereby, the characterization of a particular factor was based on answers given by most professionals.…”
Section: Definition Of the Alternatives Decision Groups And Altementioning
confidence: 99%
“…A study of global software development teams found that project managers consider task size, autonomy, expertise, and variety of work when allocating tasks to developers [21]. Another study found that managers consider business expertise and the developer's technical knowledge when allocating tasks in global software development [35].…”
Section: Introductionmentioning
confidence: 99%